Semiotik Lagu Bungan Sandat sebagai Media Pembelajaran Mendalam untuk Membentuk Dimensi Profil Lulusan Berbasis Tri Hita Karana - Abdy, Iwan; Bestari, Ida Ayu Purnama; Kiswara, Komang Agus Triadi; Hermawan, I Made Surya; Andang, Andang; Wardani, Ni Nyoman Alit Putri; Ramdhani, Lisda; Purnami, Ketut Manis Santi; Sutajaya, I Made (LPPM Institut Pendidikan Nusantara Global, 2025)
This study analyzes the utilization of the Balinese traditional song “Bungan Sandat” composed by Anak Agung Made Tjakra as a medium for deep learning aimed at shaping graduate profile dimensions based on the Tri Hita Karana philosophy. An interpretative qualitative approach combining semiotic analysis and document review was employed to uncover linguistic signs, icons, and metaphors embedded within the song’s lyrics. The findings reveal a strong integration of the three core values, parhyangan (harmony with God), pawongan (harmony among people), and palemahan (harmony with nature), which can be mapped onto eight graduate profile dimensions: faith and piety, citizenship, critical reasoning, creativity, collaboration, independence, health, and communication. The metaphor of the kenanga flower that remains fragrant even when wilted symbolizes independence, resilience, and steadfast character. The teaching of menyama braya reinforces the values of citizenship, solidarity, and collaboration, while the emphasis on harmony with the natural environment aligns with the dimensions of health, creativity, and ecological awareness. The study offers theoretical contributions to the development of education rooted in local wisdom and provides practical insights for implementing a contextual, meaningful, and enjoyable curriculum. Ultimately, it underscores the urgency of preserving local culture as a vital source of learning to confront globalization and to cultivate graduates with a strong, culturally grounded identity and noble character.